1983
DOI: 10.1104/pp.72.4.1029
|View full text |Cite
|
Sign up to set email alerts
|

Role of Inosine Monophosphate Oxidoreductase in the Formation of Ureides in Nitrogen-Fixing Nodules of Cowpea (Vigna unguiculata L. Walp.)

Abstract: Cell-free extracts from nodules of cowpea ( Vigna unguiculata L. (Walp.) cv Caloona:Rhizobium strain CB756) prepared in the presence of 15% (v/ v) glycerol showed high rates (30 to 60 nanomoles NAD reduced per minute per gram fresh weight nodule) of inosine monophosphate oxidoreductase (EC 1.2.1.14) activity. The enzyme was labile (half-life of activity less than 3 hours) but could be stabilized for up to 18 hours by inclusion of the substrates NAD and inosine monophosphate in the breaking media. Activity sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 15 publications
1
17
0
1
Order By: Relevance
“…1, B and C) These were l/Ao to l/2o those of xanthine, indicating that IMP is likely to be metabolized principally through IMP oxidoreductase rather than by an alternative route via inosine. This is consistent with the conclusions of earlier studies on cowpea nodules (21) based on kinetic properties ofthe purified component enzymes (6) and on the production of XMP in a cell-free system (21).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…1, B and C) These were l/Ao to l/2o those of xanthine, indicating that IMP is likely to be metabolized principally through IMP oxidoreductase rather than by an alternative route via inosine. This is consistent with the conclusions of earlier studies on cowpea nodules (21) based on kinetic properties ofthe purified component enzymes (6) and on the production of XMP in a cell-free system (21).…”
Section: Resultssupporting
confidence: 93%
“…Merr.) nodules (4), together with specific purine nucleosidase (8) and enzymes of purine oxidation (IMP:oxidoreductase, xanthine oxidoreductase, and urate oxidase) (3,6,21). Although a number of studies using labeled N2 have confirmed that currently fixed nitrogen is utilized in ureide synthesis (12)(13)(14)(15)(16), none has reported the recovery of purine pathway intermediates as products of fixation.…”
mentioning
confidence: 99%
“…This is not surprising for the latter reaction because no inosine dehydrogenase has been identified in any species. However, XMP dephosphorylation has been postulated to occur when inosine monophosphate (IMP) is degraded to form ureides in nodules of ureide-exporting legumes (Shelp and Atkins, 1983) and for the generation of purine alkaloids (caffeine and theobromine) from IMP in coffee (Coffea arabica) and tea (Ito and Ashihara, 1999;Koshiishi et al, 2001;Keya et al, 2003), although direct evidence for XMP dephosphorylation in vivo is lacking. Nonetheless, all current reviews of plant nucleotide metabolism also include an XMP-to-xanthosine dephosphorylation reaction in their overview schemes (Stasolla et al, 2003;Zrenner et al, 2006;Ashihara et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Inosine monophosphate dehydrogenase (IMPDH) activity was detected as described by Shelp and Atkins (1983) in 1 ml of reaction mixture containing 100 mM Tris-HCl (pH 7.2), 100 mM KCl, 2 mM inosine monophosphate, 1 mM NAD, 3 mM EDTA, 1 mM DTT, and 10 lg of protein extract. The increase in absorbance due to NADH synthesis was detected at 340 nm for 3 min.…”
Section: Detection Enzyme Activities Involved In Basal Metabolismmentioning
confidence: 99%